An Assessment of High-Risk Sexual Behavior and Associated Factors Among Self-identified Hijras Residing in an Urban Slum of Mumbai, India - Deepak K. Mundhe; Saniya S. Qureshi; Yuvaraj B. Chavan (Indian Journal of Community Medicine, 2025)
Background: A high proportion of sexual minorities like Hijras/Eunuch engage in sex work and thus become a high-risk population for HIV and sexually transmitted infections (STIs). Hence, we conducted a study with objective to assess prevalence of high-risk behavior among self-identified Hijras/Eunuch and associated factors. Material and Methods: A cross-sectional study was conducted in a field practice area of Tertiary Care Hospital from December 2019 to December 2020. All participants in the age group of 18 to 45 years were interviewed. Univariate and bivariate analysis was done to determine the correlates. Results: Out of 163, 85% of participants were involved in high-risk sexual behavior and 46.63% did only sex work, 51.5% of participants had comprehensive knowledge about HIV/STI. On applying logistic regression, the factors associated with high-risk sexual behavior include 18–24 years of age group, history of addiction, practicing paid sex, using psychotropic substances, comprehensive knowledge regarding HIV/STI, and comprehensive exposure to preventive measures. Conclusion: Our study ﬁndings suggest the urgent need for appropriate preventive measures to understand and address sexual health and risk behavior vulnerabilities faced by Hijras to make signiﬁcant progress against the HIV epidemic in the country.